من أعلام الزيتونة : الشيخ سالم بن حميدة الأكودي وجهوده الإصلاحية . From Zaytouna Flags : Sheikh Salem Bin Hamida Al Akoudi And His Reform Efforts - محي الدين, عباسي (جامعة الوادي university of eloued, 2023)
ملخص : يقتضي الواجب تسليط الضوء على خصوصية التجربة التونسية النّموذجية في تحقيق النهضة الثقافية والفكريّة والإصلاحية، وإثراء الذاكرة الجماعية الوطنية التونسية، وتكريم جيل الروّاد من صانعي ربيع الاستقلال الوطني، ومن بينهم الشيخ سالم بن حميدة الأكّودي من منطقة الساحل التونسي من مدينة أكودة بولاية سوسة التي ينتمي إليها، وهذا فيه إشارة واضحة لإبراز دور المدن والقرى والبلدات التونسية كل من موقعها وضمن خصوصياتها في الحركة الإصلاحيّة الوطنية. جمع الشيخ بن حميدة بين سمات الفيلسوف المتصوّف المُقبل على الحياة والدّاعي إلى إعمال العقل والتّجديد، إضافة الى نشاطه الوطني في النّضال من أجل تحرير المجتمع من التخلّف والوطن من الاستعمار، فضلا عن دوره في الحثّ على الحريّة والعدالة والتسامح والحوار بين الحضارات والشّعوب، تتلمذ على يديه الطاهر الحداد صاحب كتاب "امرأتنا في الشريعة والمجتمع"، وعبد الرزاق كرباكة صاحب جريدة الزمان الفكرية والأدبية وغيرهم... كما ترك الشيخ سالم بن حميدة آثارا أدبيّة وفكريّة تمثّلت في: "ديوان الزهريّات"، متكوّن من مقالات نثريّة وقصائد شعريّة تحوصل مجمل أفكاره الإصلاحية، كما كتب في الصحف التونسيّة الصّادرة في عصره، وهو علم من أعلام الزيتونة . Abstract : It is necessary to highlight the specificity of Tunisia's exemplary experience in achieving cultural, intellectual and reformist renaissance. and to enrich Tunisia's national collective memory and honour the pioneering generation of makers of the spring of national independence Shaikh Salem bin Hamida al-Akudi of Tunisia's Sahel region from Akoda, Sousse State, This is a clear indication of the role of Tunisia's cities, villages and towns, both in their location and within their specificities, in the national reform movement. Sheikh Ben Hamida combines the features of the future mystical philosopher for life and advocates for the realization of reason and renewal, as well as his national activism in the struggle for the liberation of society from underdevelopment and homeland from colonialism, as well as his role in the promotion of freedom, justice, tolerance and dialogue among civilizations and peoples, apprenticed to the hands of the clean mourse. "Our Woman in Shari 'a and Society", Abd al-Razaq Karbakah, owner of Al-Timor Intellectual and Literary Newspaper and others... Sheikh Salem bin Hamida also left literary and intellectual traces: "The Office of the Flowers", consisting of prose articles and poetry poems that capture all his reform ideas, as he wrote in Tunisian newspapers of his time, a flag of olive flags
مقال
Keywords: أعلام؛ الزيتونة؛ الأكودي؛ جهود؛ إصلاح; flags; olive; Acode; Efforts; Repair.